Annual faculty research recognition program - University Research Coordination Office - De La Salle University, Manila (Animo Repository, 1995)
The University Research Coordination Office awarded certificates to 67 faculty researchers who had completed projects for the period March 2, 1994 to February 20, 1995. The program had Dr. Osteria spoke on Education Beyond the Classroom: The Challenges of Research. The activity was part of the Mission Statement-University Week, 1995 celebrations.